2020
DOI: 10.3389/fpsyt.2020.00714
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Disorders and COVID-19: Multi-Faceted Problems Which Require Multi-Pronged Solutions

Abstract: COVID-19 shocked health and economic systems leaving millions of people without employment and safety nets. The pandemic disproportionately affects people with substance use disorders (SUDs) due to the collision between SUDs and COVID-19. Comorbidities and risk environments for SUDs are likely risk factors for COVID-19. The pandemic, in turn, diminishes resources that people with SUD need for their recovery and wellbeing. This article presents an interdisciplinary and international perspective on how COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 111 publications
4
100
1
Order By: Relevance
“…Psychosocial distress might be particularly challenging for patients with SUDs, since social distancing and quarantine might intensify isolation and loneliness (32). In this context, living alone is associated with a greater risk of suffering from SUDs in older adults (33).…”
Section: Impact Of Covid-19 On Addictive Behaviors and Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial distress might be particularly challenging for patients with SUDs, since social distancing and quarantine might intensify isolation and loneliness (32). In this context, living alone is associated with a greater risk of suffering from SUDs in older adults (33).…”
Section: Impact Of Covid-19 On Addictive Behaviors and Disordersmentioning
confidence: 99%
“…In fact, studies on economic crises found associations between an increase in unemployment with a substantial increase (28%) in mortality due to SUDs and higher numbers of suicide (4.5%) (34). Additionally, the pandemic disproportionately affects people with SUDs by diminishing resources that people with SUD need for their recovery and wellbeing (32).…”
Section: Impact Of Covid-19 On Addictive Behaviors and Disordersmentioning
confidence: 99%
“…From our perspective, during lockdown only the main pharmacological supply of these patients was enabled, while long-term treatment including psychological and psychiatric support was nearly impossible due to restricted access to all outpatient clinics. For the future, it is important to provide patients suffering from addictive disorders with all possible resources in order to maintain a high standard in addiction care practice, including use of telehealth and adopting proactive policies (3). In this context, we strongly recommend the EMCDDA's conclusion that developments in the area of PWUD due to COVID-19 should be closely monitored in respect to potential risky and hazardous patterns of use (23).…”
Section: Patients In Opioid Substitution Treatment: Misuse and Concommentioning
confidence: 99%
“…The impact of COVID-19 might be particularly challenging for vulnerable populations (1) including people suffering from substance use disorder (SUD) (2). The reciprocal impact between Covid-19 and SUD have been described, categorized in spread of disease, risk of infection, increased severity of COVID-19 symptoms, psychological stress, and reduced access to addiction treatment services (3). Reports from different countries suggest reduced availability of illicit and prescribed drugs, altered consumption patterns, higher probability of relapse, and even elevated risk of deadly overdose without opportunity for rescue due to social distancing and isolation (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…And the epidemic of substance use disorders (SUDs) related to COVID-19 is not confined to the US; there are similar reports from other afflicted nations, making addiction truly the other pandemic. 4 The Centers for Disease Control and Prevention reported that 13.3% of American adults have started or increased their substance use as a means of managing the negative emotions associated with the pandemic. 5 Also from March to May 2020, researchers in Baltimore found a 17.6% increase in suspected overdoses in counties advising social distancing and/or mandating stay at home orders.…”
mentioning
confidence: 99%